Self-congruence facets and emotional brand attachment: The role of product involvement and product type - Muhammad Sheeraz; Faisal Qadeer; Mirha Masood; Imran Hameed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Consumers have emotional bond with the brands that are closer to their self-concept. The product involvement is consumers' perception of relevance of a product with needs, goals and consumers' self-concept. Therefore, the study aims to reconsider the role of product involvement in the association of self-congruence facets and emotional brand attachment. Furthermore, the study investigates the association of self-congruence facets and emotional brand attachment depending upon product type. The study followed a mixed method research approach and involved a focus group study and a survey. Hypotheses testing (through AMOS and Process Macro) indicated that ideal self-congruence yielded substantial influence on product involvement and emotional brand attachment. Whereas, ideal self-congruence direct effect on emotional brand attachment turned out to be insignificant in presence of mediator. Furthermore, the effect of product involvement on emotional brand attachment significantly depends upon product type. The conditional indirect effect of self-congruence facets was stronger for hedonic brands as compared to utilitarian brands. The study contributes to marketing literature by discovering product involvement as processing mechanism between the debate of self-congruence facets and emotional brand attachment. The study is first in nature to investigate the moderating role of product type in the relationship and exploring conditional indirect on emotional brand attachment.
Keywords: 330; actual self-congruence; ideal self-congruence; product involvement; emotional brand attachment; hedonic brands; utilitarian brands; Pakistani consumers